Pengembangan Aplikasi Pengendalian Mutu Uji Terowongan Angin Kecepatan Rendah Indonesia - Pane, Ivransa Zuhdi (STMIK Budi Darma, 2020)
Quality control in the wind tunnel test service in the Indonesian Low Speed Tunnel plays an important role to produce good test results, but it is still being done in a manual and traditional way. As a result, there are still problems in the implementasion and evaluation of quality control of a wind tunnel test. The quality control which is managed by utilizing information technology can not only solve such problems, but also encourage productivity and performance of quality control unit personnel in carrying out their duties. The development of quality control applications as a form of utilizing information technology through software engineering stages, starting from requirements analysis, design, construction and software testing, is expected to be able to realize contemporary quality control mechanisms and integrated with other information management activities which in turn support the management in executive decision making